Clinical and laboratory assessment of the effect of hygiene products on the condition of periodontal tissues and hard tooth tissues in the treatment of caries by indirect method - I. A. Belenova; V. A. Mitronin; Z. A. Filippova; V. I. Khryachkov; M. S. Vasilyeva; N. A. Protsenko (Эндодонтия Today)
Relevance. According to statistics, the widespread use in modern dental practice of indirect restoration methods in the treatment of caries of the frontal group of teeth leads to an increase in the incidence of marginal periodontal disease. According to modern data, the most important etiological factor in the development of complications from the hard tissues of the tooth and periodontal is the microflora of plaque.The main link in carrying out preventive measures and the guarantee of the quality of the rehabilitation period is an adequate choice of personal oral hygiene products. It is for this reason that, when choosing a preventive program and personal hygiene products, especially in patients with extensive restorations (including indirect ones), more and more attention is currently being paid to toothpastes based on medicinal herbs, aluminum lactate, which have an anti-inflammatory, astringent effect, reducing bleeding gums and hyperesthesia of hard tooth tissues.Aim. Comparison of the clinical effectiveness of the standard prevention program and the prevention program using individual oral hygiene products based on aluminum lactate in the treatment of caries by the indirect method, as well as improving the effectiveness of indirect methods of caries treatment by preventing its recurrence and inflammatory complications from periodontal tissues by developing practical recommendations.Materials and methods. The work was carried out in the design of an open comparative three-stage prospective nonrandomized study. The necessary material was collected using clinical, laboratory and statistical methods. The material for the study was 98 patients with indirect restorations of the frontal group of teeth, of which 46 people had restoration from metal-free ceramics E-max and 52 people from pre-polymerized composite and divided into groups according to the hygienic means used and the type of restoration. A micronuclear test in the gingival epithelium with the establishment of the frequency of occurrence and spectrum of nuclear aberrations in the cells of the gingival epithelium was carried out in vitro. Statistical data processing was carried out using standard packages Statistika 8.1 and SPSS-11.Results. Based on the results of 2236 clinical and 550 laboratory studies stating the condition of the hard tissues of the tooth, the tooth-restoration boundary, the tissues of the marginal periodontal and the evaluation of the effectiveness of the hygiene product used, the results of statistical processing and the use of high technologies to solve the tasks, it can be said that traditional means of individual oral hygiene have sufficient effectiveness when used in preventive program of recurrence of carious process and periodontal diseases, but significantly higher with a statistically significant difference in effectiveness, especially in terms of anti-inflammatory action, are products containing aluminum lactate, which has a direct and direct impact on the quality of restoration and dental rehabilitation of the patient even 24 months after treatment.Conclusions. Personal oral hygiene products containing aluminum lactate, which has pronounced astringent and antiinflammatory properties. These remedies should be the subject of choice in the most difficult clinical situations, such as diagnosed periodontal diseases with the preservation of complaints (pain, bleeding gums, unpleasant odor, etc.), low level of oral hygiene, rehabilitation period after periodontal treatment, prevention of periodontal diseases in patients with extensive restorations. The use of personal oral hygiene products containing aluminum lactate will significantly improve the effectiveness of treatment and prevention of caries including indirect methods, reduce the risk of repeated invasions and ensure full-fledged dental rehabilitation of the patient directly affecting his quality of life.